Fenomenologi Kepemimpinan Kepala Lembang Perempuan Pada Masa Pandemi Covid-19 di Kabupaten Toraja Utara - Marlina Bubang; Leonardo Paundanan (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: The phenomenon of the leadership of the female village head during the Covid-19 pandemic in North Toraja, so the writer formulates the problem of how the experiences and feelings of women leaders in carrying out their duties in the midst of the Covid-19 pandemic as heads of village and the purpose of this research is to find out the experiences and feelings of female leaders in carrying out their duties in the middle of the Covid-19 pandemic as heads of village in North Toraja. The research method used by the author is qualitative with a phenomenological approach. The results of the study prove that women are often stereotyped as creatures who has no ability to be a leader, but in reality several woman in North Toraja were able to take the heads of village during the Covid-19. The existence of Covid-19 can cause several obstacles for leaders, specifically female village heads in North Toraja both in terms of working time and in terms of coordination between village officials. However, they still carry out their duties and responsibilities both directly (face to face) and online by utilizing communication technology to coordinate with village officials during the Covid-19 pandemic. Keywords: Leadership, Feminist Leadership, Head of Lembang Abstrak: Adanya fenomena kepemimpinan kepala lembang perempuan pada masa pandemi Covid-19 di Toraja Utara, sehingga penulis merumuskan masalah bagaimana pengalaman dan perasaan pemimpin perempuan dalam melaksanakan tugasnya di tengah pandemi Covid-19 sebagai kepala lembang dan tujuan penelitian ini adalah untuk mengetahui pengalaman-pengalaman dan perasaan pemimpin perempuan dalam melaksanakan tugasnya di tengah pandemi Covid-19 sebagai kepala lembang di Toraja Utara. Metode penelitian yang dipakai penulis adalah kualitatif dengan pendekatan fenomenologi. Hasil penelitian membuktikan bahwa perempuan yang kerapkali distereotipekan sebagai sosok yang tidak memiliki kemampuan untuk menjadi seorang pemimpin, namun kenyataannya beberapa perempuan di Toraja Utara dapat memimpin sebagai kepala lembang pada masa pandemi Covid-19. Adanya Covid-19 dapat menimbulkan beberapa kendala bagi pemimpin, secara khusus kepala lembang perempuan di Toraja Utara baik dari segi waktu kerja maupun dari segi koordinasi antar-aparat lembang. Meski demikian, kepala lembang tetap melaksanakan tugas dan tanggung jawab mereka sebagai pemimpin baik secara langsung (tatap muka) maupun secara online dengan cara memanfaatkan teknologi komunikasi untuk berkoordinasi dengan aparat lembang pada masa pandemi Covid-19. Kata kunci: Kepemimpinan, Kepemimpinan Perempuan, Kepala Lembang